NEURO ENGINEERING TECHNOLOGY TO ACCELERATE THE HUMAN ADAPTATION TO HIGH ALTITUDE HYPOXIA - Mukhamed T. Shaov; Olga V. Pshikova (Юг России: экология, развитие, 2018)
Abstract. The aim is to study the influence of neuro-information signals modulated by pulse hypoxia on the rhythm of cardiac contractions in low-mountain and high-mountain conditions. Methods. Heart rate was measured using the pulse oxymetry device ELOX-01M2. The impact analysis of information-wave signals was carried out with the help of the neuro-protector "Anthropotherapist", non-invasively (remotely) at a distance of up to 5 meters for 5 min. /day during 10 days. The investigations were carried out in lowmountain conditions (city of Nalchik, 550 m above sea level) and highlands, Mount Elbrus (site of "Garabashi", 3780 m. above sea level). Participants in the study were divided into groups: control group – 18 participants; experimental group - 18 participants. In the low-mountain and high-mountain conditions, the control group was not affected by the neuro-protector. In high-mountain conditions, the participants in the control group experienced only the effects of high-altitude hypoxia sessions. The experimental group was exposed to the neuro-information signals from the neuro-protector. High-altitude studies were carried out in the following mode: heart rate was recorded at the altitudes of Nalchik - exit to Elbrus – on the way to the site of "Garabashi" - return route to Nalchik. Results. It was found that with frequency exposure, there is a significant decrease and fluctuations in heart rate in low-mountain inhabitants. The stability of these changes in the rhythm of cardiac activity can also be seen in conditions of high-altitude hypoxia. Conclusion. Consequently, the proposed mode of frequency impact, implemented using the "Anthropotherapist" neuro-protector technology, can form a stage of adaptation to hypoxia and unfavorable climatic and environmental factors.